Study of Zn-Pb ore tailings and their potential in cement technology. (March 2018) - Nouairi, J.; Hajjaji, W.; Costa, C.S.; Senff, L.; Patinha, C.; Ferreira da Silva, E.; Labrincha, J.A.; Rocha, F.; Medhioub, M.
Abstract: This paper describes the synthesis of sulfobelite clinkers incorporating mining rejects. The targeted Zn-Pb tailing wastes generated in the diapiric zone (NW Tunisia) were tested in clinker/cement compositions to ensure the inertization of existing hazardous heavy metals. Mineralogical composition of the two selected samples revealed calcite, dolomite, quartz, kaolinite, galena, pyrite and gypsum as crystalline phases. Vertical distributions of dominant heavy metals (Pb, Zn and Cu) in soil profiles show enrichment in the surface layers and decrease towards the depth. In sintered clinkers powders, the presence of the targeted crystalline phases (trialuminate sulphate (C4A3Š), belite (C2S), and ferrite (C4AF)) are in the predicted desirable amounts. Heat flow generated during the hydration of different cement pastes showed a slower reaction for clinkers with higher amounts of C4 A3 Š or constituted by coarser particles. After 28 days curing, the best mechanical resistance (24.34 MPa under compression) was obtained for the clinker calcined at 1350 °C and showing a suitable particle size distribution. Concerning heavy metals, immobilisation of 75–85% of Pb, Zn and Cu was assessed in the mortars formulated with the produced clinker/cement, posing no hazardous risks to the environment. Highlights: The synthesis of sulfobelite clinkers is incorporating mining rejects. Clinkers are composed of C4 A3 Š, C2 S, and C4 AF as predicted by initial formulations. Mechanical strength reached high values after 28 days curing, superior to 15 MPa. Pb, Zn and Cu heavy metals immobilisation was superior to 75% in produced mortars.